Industrial data communications - Thompson, Lawrence M.; Shaw, Tim (International Society of Automation (ISA), 2016)
This Edition will help you gain a solid understanding of legacy and advanced communications systems in automation and control environments as well as the advances in communication technology. You will learn about cybersecurity methods and standards - including ANSI/ISA/IEC 62443 - and how to implement communications systems in a safe and secure manner.